Colletotrichum aotearoa B. Weir & P.R. Johnst causing leaf anthracnose in Lithocarpus litseifolius in China - Yuling Wang; Chang Liu; Guolin Cai; Ning Shu; Ziqiang Luo; Zixuan Qiu; Wuping Yan (Crop Protection, 2026)

Spatially resolved multi-omics analysis of indigenous Bacillus-fortified high-temperature Daqu - Hao Shi; Yuling Shen; Qingqing Ye; Hui Yu; Maoling Tian; Hongmei Wang; Yang Wei; Shiying Yan; Yiping Chen; Jie Zhang; Shu Li; Yang Yang; et al. (Food Research International, 2026)

Metabolic reprogramming for post-acidification control in fermented milk via post-sterilization treatment - Han Lu; Liru Cui; Menglu Li; Yuling Xue; Yannan He; Chang Liu; Yan Wu; Shijie Wang (Food Microbiology, 2026)

Multi-omics insights into key aroma compound formation during Chinese bayberry wine fermentation by Pichia kluyveri ZFM-0524 - Shuxun Liu; Mingfeng Cao; Yan Zhao; Yufeng Xu; Luan Zhang; Yuling Cai; Qing Gu (International Journal of Food Microbiology, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Explainable machine learning-based study on the applicability of thermal indicators for university classrooms in summer - Luyao Wang; Fan Fei; Yan Wang; Yongwei Song; Yuling Xiao; Weidong Wu; Kunkun Zhao; Hiroatsu Fukuda (Building and Environment, 2026)

Improving embryo rescue efficiency in seedless grape breeding with zeatin - Xi Chen; Shaopeng Zhao; Xinyu Chen; Mengyu Ma; Xue Wen; Yao Xiao; Yong Wang; Yuling Li; Feng Sun; Guotian Liu; Tingting Chen; Yan Xu (Protoplasma, 2026)

Clinical study on the interaction between iron metabolism and neuroinflammation and iron deposition in the substantia nigra of Parkinson’s disease - Yani Yao; Jiayi Li; Jiaoyang Yan; Qian Cai; Yuling Wang; Huan Xia; Tingting Feng; Peishan Li; Xinling Yang (Brain Imaging and Behavior, 2026)

The pulse of ancient fires: Reconstructing Toarcian wildfire regimes from fossil charcoals in northwest China - Yuling Na; Xiao Shi; Chi Tian; Wenpei Pei; Qianqian Song; Shaoting Tian; Bing Wang; Yan Liu; Leon Nahuel Torres; Jianxin Yu (Review of Palaeobotany and Palynology, 2026)

Shoot apical meristem-dependent adventitious bud induction from embryo axes of castor bean (Ricinus communis L.) via optimized cytokinin-auxin ratio - Liang Bai; Liying Shan; Jian Song; Mengchen Xu; Yue Wang; Ruiyan Guo; Yanli Jin; Yangguang Duan; Yuling Zhang; Zhimin Jiang; Jilong Zhong; Yan Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Epicoccum sorghinum as a leaf spot disease-causing pathogen in Lithocarpus litseifolius in China - Yuling Wang; Meng Li; Changjiang Liu; Guolin Cai; Mengxing Wang; Wuping Yan; Jianfeng Chen (Crop Protection, 2026)

Identification, antioxidant and acetylcholinesterase inhibitory activities of soluble and insoluble-bioactive components from Cinnamomum camphora seed kernel residue - Pinpin Zhang; Junmin Long; Zheling Zeng; Xianghui Yan; Yujing Yang; Rongping Fu; Yuling Lin; Deming Gong; Cheng Zeng; Ping Yu (Food Research International, 2026)

Molecular Dissection of Response Mechanism and Leaf Color Variation in Ulmus Pumila Cv.‘Jinye’ Under Saline-Alkali Stress - Shufang Yan; Yichao Liu; Shuxiang Feng; Gongdan Zhou; Yuling Li; Yinran Huang (Journal of Crop Health, 2026)

A novel antiviral peptide Laby A1/A3 precursor-SUMO against PCV2 replication with broad-spectrum antiviral potential - Yan Zhang; Yuling Li; Qiqi Xia; Jingyuan Zhang; Yanmin Li; Long Zhou; Zijing Guo; Zhidong Zhang (Veterinary Microbiology, 2026)

Hybrid evaporative-fan cooling vest: multi-scale cooling performance evaluation - XingLan Wang; Guang Yang; ShouXin Zhang; XiaoShan Yan; Yuling Luo; Suqin Chang; Xiaohui Zheng (Energy and Buildings, 2026)

Utilizing phosphogypsum-derived CaAl LDH-chitosan to remove Pb2+ from oil/gas field wastewater: Adsorption behavior and competitive mechanism - Jing Bai; Qijia You; Yushuan Peng; Zhihao Li; Yuling Zhang; Qiulin Deng; Huiwei Liao; Faqin Dong; Xiaofeng Zeng; Zixun Yan (Process Safety and Environmental Protection, 2025)

Hydro-mechanical degradation and crack evolution in undisturbed loess induced by multiple wet-dry cycle paths - Zhou Chang; Changgen Yan; Hengxing Lan; Yuling Shi; Han Bao; Ning An; Zhuolong Jia (Bulletin of Engineering Geology and the Environment, 2025)

Confinement-effect adsorbents based on titanium-based lithium ion sieve for efficient lithium adsorption under natural pH conditions - Yuling Ma; Yu Han; Yan Yang; Tao Zhang; Jinxin Yao; Yuchen Li; Yongchen Zong; Wei Wang (Chemical Engineering Journal, 2025)

KHDC3 affects the lineage differentiation of early embryo by regulating the differential distribution of YAP signal - Qian Xu; Yuling Lin; Lina Yu; Yang Zhang; Na Kong; Guijun Yan; Haixiang Sun; Guangyi Cao (Theriogenology, 2025)

Fractional-order constitutive model of loess creep incorporating microstructural damage under seepage-stress coupling effect - Zhou Chang; Changgen Yan; Hengxing Lan; Shengwen Qi; Han Bao; Yuling Shi; Weifeng Sun (Engineering Geology, 2025)

Momordica Charantia L.-derived extracellular vesicles achieve pancreatic-targeted delivery and repair insulin-secretory function through dual mechanisms via lymphatic transport - Meiqi Han; Jiahong Wang; Zihan Zhang; Ziwei Yan; Zhiqi Wang; Xinyao Guan; Siling Wang; Yuling Mao; Jinghai Zhang (Chemical Engineering Journal, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Study on water temperature variation trend and disturbance patterns in hydropower development section of the upper Yellow River - Chenxu Zhao; Yuling Liu; Ce Song; Zixuan Yan (Ecohydrology & Hydrobiology, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Correction to: Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

Comparative transcriptomic analysis of heterotic maize development during kernel filling - Wenyu Li; Xiangkun Guo; Wen Yao; Keke Li; Qi Zheng; Yongbiao Yu; Zhiwei Zhang; Yan Wang; Weigang Yao; Ju Wu; Huan Hu; Lingwei Hu; et al. (Plant Molecular Biology, 2025)

Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

Coniferous wood fossils as records of paleoecology, paleoclimatology, and paleoenvironment: A review - Leon Nahuel Torres; Xiao Shi; Yuling Na; Bing Wang; Chi Tian; Wenpei Pei; Yan Liu; Jianxin Yu (Review of Palaeobotany and Palynology, 2025)

Design and performance analysis of novel morphing wing driven by modular deployable mechanism for underwater gliders - Hongyu Wu; Xueao Liu; Yuxing Hao; Maolin Liao; Wendong Niu; Yuling Zhang; Shaoze Yan (Ocean Engineering, 2025)

Influences of natural organic acids on the degradation of atrazine in water by pyrite-mediated Fenton oxidation - Yuling Zheng; Fang Li; Chen Yan; Wei Yang; Jia Wen; Biao Song (Journal of Water Process Engineering, 2025)

Interface performance and damage strength model of guar gum−treated fiber−reinforcement loess slope protection material - Huaixin Li; Changgen Yan; Jing Ren; Yuling Shi; Han Bao; Zhuolong Jia; Zherui Liang (Journal of Cleaner Production, 2025)

In-situ air bubble for efficient membrane scaling cleaning with a catalytic nanofiber membrane in membrane distillation - Zhongsen Yan; Ziyue Zhang; Yaman Huang; Haiqing Chang; Dan Qu; Yuling Jiang; Hongting Wan; Senlin Shao; Fangshu Qu (Desalination, 2025)

Experimental study on hydrophysical properties and slope planting of ecological composite material solidified loess - Changgen Yan; Jinhui Zhao; Zhuolong Jia; Hengxing Lan; Han Bao; Yuling Shi (Journal of Environmental Management, 2025)

Eliminating the effect of pH: Dual-matrix modulation adsorbent enables efficient lithium extraction from concentrated seawater - Yu Han; Liuqian An; Yan Yang; Yuling Ma; Hongliang Sun; Jinxin Yao; Tao Zhang; Wei Wang (Water Research, 2025)

The tomato gene Ty-6, encoding DNA polymerase delta subunit 1, confers broad resistance to Geminiviruses - Xuexue Shen; Upinder Gill; Marjon Arens; Zhe Yan; Yuling Bai; Samuel F. Hutton; Anne-Marie A. Wolters (Theoretical and Applied Genetics, 2025)
Key message The tomato Ty-6 gene conferring resistance against begomoviruses has been cloned and shown to be a variant of DNA polymerase delta subunit 1. Abstract Ty-6 is a major resistance gene of tomato that provides resistance against monopartite and bipartite begomoviruses. The locus was previously mapped on chromosome 10, and in this study, we fine-mapped Ty-6 to a region of 47 kb, including four annotated candidate genes. Via whole-genome resequencing of Ty-6 breeding lines and several susceptible breeding lines, the polymorphisms in gene sequences were discovered and gene-associated markers were developed for marker-assistant breeding. Further, virus-induced gene silencing and candidate gene overexpressing in susceptible tomatoes revealed that Ty-6- mediated resistance is controlled by Solyc10g081250, encoding the DNA polymerase delta subunit 1, SlPOLD1 . The single nucleotide polymorphism of Ty-6 results in an amino acid change that might influence the fidelity of virus DNA replication.

Selective ion channel adsorbents facilitate efficient and low environmental impact extraction of liquid lithium resources - Yu Han; Yan Yang; Yuling Ma; Daxin Liang; Liping Wen; Jun Ma; Wei Wang (Journal of Hazardous Materials, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Assessment of genetic diversity of Camellia yuhsienensis based on leaf structure and inter simple sequence repeat (ISSR) markers - Yuling Zou; Xiaoning Ge; Chao Yan; Qiuping Zhong; Danyang Chen; Zexin Chen; Yaqi Yuan; Hongyan Guo; Youcheng Zhou; Jinfeng Wang; Linqing Cao (Genetic Resources and Crop Evolution, 2024)

Determining optimal nitrogen concentration intervals throughout lettuce growth using fluorescence parameters - Peizhe Li; Zhangtong Sun; Yongxia Yang; Miao Lu; Huimin Li; Haoran Yan; Jin Hu; Yuling Song (Computers and Electronics in Agriculture, 2024)

Ecological impacts of vermiculite and submerged macrophytes on sediment enzyme activity in lake restoration: Insights from the mesocosm study - Chenxu Zhao; Yuling Liu; Zixuan Yan; Wangben Zhao; Jiayu Sun (Journal of Water Process Engineering, 2024)

A novel approach for quantifying the influence intensity of urban water and greenery resources on microclimate for efficient utilization - Fan Fei; Yuling Xiao; Luyao Wang; Yan Wang; Hiroatsu Fukuda; Wanxiang Yao; Haiming Yu; Qiwei Dong (Sustainable Cities and Society, 2024)

Combining effects of submerged macrophytes and lanthanum-modified bentonite on sediment enzyme activity: Evidence from mesocosm study - Chenxu Zhao; Yuling Liu; Zixuan Yan; Wangben Zhao; Jiayu Sun (Chemosphere, 2024)

Pre-introducing Li4NiWO6 defect phase by tungsten modification enables highly stabilized Ni-rich cathode - Fanghui Du; Hanyu Qu; Xiaoxuan Yu; Lei Ding; Pengfang Zhang; Yan Wang; Yuling Chen; Yingchao Wang; Xitong Zhang; Junwei Zheng (Chemical Engineering Journal, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Influence of aggregate characteristics on the plant growing environment of the planting concrete with SAC - Shanshan Jin; Yang Zhang; Yuling Yan; Zengmiao Xu; Aodong Li; Juan Wang; Pengfei Liu; Liuhuan Li; Zhihua Wang (Journal of Cleaner Production, 2024)

Investigating alcohol consumption in China via wastewater-based epidemiology - Yan Yao; Jingya Wang; Yuling Zhong; Wenyu Chen; Yulan Rao; Mengxiang Su (Environmental Geochemistry and Health, 2024)

The relationship between antidepressants and breast cancer: evidence from Mendelian randomization - Dong Niu; Chenchen Li; Xiaoyu Yan; Haoran Qu; Yuling Zheng (Cancer Causes & Control, 2024)
Background The use of antidepressants has increased over the years, but the relationship between antidepressant use and the risk of breast cancer is not uniform because of confounding factors. We aimed to assess the effect of antidepressants on breast cancer risk using a two-sample Mendelian randomization (MR) approach.stet Methods Secondary data analysis was performed on pooled data from genome-wide association studies based on single-nucleotide polymorphisms that were highly correlated with antidepressants, SSRI drugs, and serotonin and prolactin levels were selected as instrumental variables to evaluate the association between antidepressants and SSRI drugs and prolactin levels with breast cancer and ER+/ER- breast cancer. We then performed a test of the hypothesis that SSRI drugs elevate prolactin concentrations. We performed two-sample Mendelian randomization analyses using inverse variance weighting, MR-Egger regression, and weighted median methods, respectively. Results There was no significant risk association between antidepressant and SSRI use and the development of breast cancer, ER-positive or ER-negative breast cancer ( P > 0.05), and serotonin concentration was not associated with breast cancer risk ( P > 0.05). There was a positive causal relationship between prolactin levels and breast cancer (IVW, P = 0.02, OR = 1.058) and ER-positive breast cancer (Weighted median, P = 0.043, OR = 1.141; IVW, P = 0.009, OR = 1.125). Results in SSRI medication and prolactin levels showed no association between SSRI analogs and prolactin levels ( P > 0.05). Conclusion Large MR analysis showed that antidepressants as well as SSRI drugs were not associated with breast cancer risk and the SSRI-prolactin-breast cancer hypothesis did not hold in our analysis.

A chronostratigraphic and biostratigraphic framework for the Yanliao Biota of northeastern China: Implications for Jurassic terrestrial ecosystems and evolution - Yuling Li; Su-Chin Chang; Haichun Zhang; Jun Wang; Rui Pei; Daran Zheng; Yan Fang; Sidney R. Hemming (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Application of wastewater-based epidemiology to estimate the usage of beta-agonists in 31 cities in China - Yuling Zhong; Chenzhi Hou; Xinyi Gao; Mingyu Wang; Yan Yao; Mengyi Chen; Bin Di; Mengxiang Su (Science of The Total Environment, 2023)

Surface engineering based on element interdiffusion and interfacial reactions to boost the performance of LiCoO2 cathode material - Fanghui Du; Zhongxu Fan; Lei Ding; Yan Wang; Wenjing Shi; Jie Zhang; Hanyu Qu; Xiaoxuan Yu; Yuling Chen; Junwei Zheng (Chemical Engineering Journal, 2023)

Dkk-1–TNF-α crosstalk regulates MC3T3E1 pre-osteoblast proliferation and differentiation under mechanical stress through the ERK signaling pathway - Yeke Wu; Zheng Jing; Disi Deng; Jin Yan; Min Liu; Li Li; Yuling Zuo; Wenbin Wu; Qiongying Hu; Yunfei Xie (Molecular and Cellular Biochemistry, 2023)

A new method for evaluating the synergistic effect of urban water body and vegetation in the summer outdoor thermal environment - Fan Fei; Luyao Wang; Yan Wang; Wanxiang Yao; Hiroatsu Fukuda; Yuling Xiao; Lei Tian; Tongtong Ji (Journal of Cleaner Production, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Performance test and effect evaluation of guar gum-stabilized loess as a sustainable slope protection material - Zhuolong Jia; Changgen Yan; Bo Li; Han Bao; Hengxing Lan; Zherui Liang; Yuling Shi; Jing Ren (Journal of Cleaner Production, 2023)

Spatio-temporal variations of activity of nitrate-driven anaerobic oxidation of methane and community structure of Candidatus Methanoperedens-like archaea in sediment of Wuxijiang river - Haixiang Cheng; Yuling Yang; Yefan He; Xugang Zhan; Yan Liu; Zhengfeng Hu; Hechen Huang; Xiaochen Yao; Wangting Yang; Jinghao Jin; Bingjie Ren; Jiaqi Liu; et al. (Chemosphere, 2023)

Effects of land-use change on carbon emission and its driving factors in Shaanxi Province from 2000 to 2020 - Chenxu Zhao; Yuling Liu; Zixuan Yan (Environmental Science and Pollution Research, 2023)

GRK5 Deficiency in the Hippocampus Leads to Cognitive Impairment via Abnormal Microglial Alterations - Hongtao Shen; Tianzhen Zhang; Yao Ji; Yu Zhang; Yongxiang Wang; Yuling Jiang; Xiongjin Chen; Qiuhao Liang; Kefeng Wu; Yunfeng Li; Xingyu Lu; Lili Cui; et al. (Molecular Neurobiology, 2023)

The increased medical burden associated with frailty is partly attributable to household solid fuel: A nationwide prospective study of middle-aged and older people in China - Xiaoyu Jin; Yuling Wang; Yudong Wu; Yunfeng Liang; Yuxuan Li; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Junwen Tao; Jian Song; Rubing Pan; Weizhuo Yi; et al. (Science of The Total Environment, 2023)

Estimating the prevalence of hypertension in 164 cities in China by wastewater-based epidemiology - Chenzhi Hou; Yuling Zhong; Lan Zhang; Muyuan Liu; Fang Yan; Mengyi Chen; Youmei Wang; Peng Xu; Mengxiang Su; Chi Hu; Bin Di (Journal of Hazardous Materials, 2023)

Hyperspectral imaging combined with chemometrics for rapid detection of talcum powder adulterated in wheat flour - Hong-Ju He; Yan Chen; Guanglei Li; Yuling Wang; Xingqi Ou; Jingli Guo (Food Control, 2023)

Atmospheric particulate matter impairs cognition by modulating synaptic function via the nose-to-brain route - Chunmei Liang; Yuling Jiang; Tianzhen Zhang; Yao Ji; Yu Zhang; Yuanhong Sun; Shengnan Li; Yi Qi; Yan Wang; Yujie Cai; Tianwen Lai; Lili Cui (Science of The Total Environment, 2023)

Synergistic effect of CoOx and Ni-Co alloy in Ni-Co/SAPO-11 catalysts for the deoxygenation of stearic acids - Dejiang Zheng; Delin Guo; Zhongxu Wang; Xiaosheng Wang; Yuling Shan; Xinmei Liu; Zifeng Yan; Shitao Yu; Yuxiang Liu (Chemical Engineering Journal, 2023)

PAH-induced metabolic changes related to inflammation in childhood asthma - Hao Wu; Yuling Bao; Tongtong Yan; Hui Huang; Ping Jiang; Zhan Zhang; Lei Li; Qian Wu (Environmental Science and Pollution Research, 2022)

PiRNA pathway in the cardiovascular system: a novel regulator of cardiac differentiation, repair and regeneration - Yuling Zhou; Ya Fang; Cuilian Dai; Yan Wang (Journal of Molecular Medicine, 2021)

Assessment of long-term functional maintenance of primary human hepatocytes to predict drug-induced hepatoxicity in vitro - Yi Chen; Dan Tang; Hongping Wu; Yuling Wu; Tianjie Yuan; Hongdan Zhang; Yingfu Jiao; Weifeng Yu; Hexin Yan (Archives of Toxicology, 2021)

Molecular characterization of miRNA genes and their expression in Dimocarpus longan Lour - Yuling Lin; Yan Chen; Youjing Zeng; Shuting Zhang; Zihao Zhang; YuKun Chen; Jiawei Gong; Zhongxiong Lai (Planta, 2021)

Inhibition of berberine hydrochloride on Candida albicans biofilm formation - Xiaoxue Huang; Mingyue Zheng; Yuling Yi; Anamica Patel; Zhen Song; Yan Li (Biotechnology Letters, 2020)

Effects of deficit irrigation combined with rainwater harvesting planting system on the water use efficiency and maize (Zea mays L.) yield in a semiarid area - Peng Zhang; Ting Wei; Yuling Li; Yan Zhang; Tie Cai; Xiaolong Ren; Qingfang Han; Zhikuan Jia (Irrigation Science, 2019)

Abnormal Brain Structure and Function in First-Episode Childhood- and Adolescence-Onset Schizophrenia: Association with Clinical Symptoms - Yanhong Xia; Dan Lv; Yinghui Liang; Haisan Zhang; Keyang Pei; Rongrong Shao; Yali Li; Yan Zhang; Yuling Li; Jinghua Guo; Luxian Lv; Suqin Guo (Neuroscience Bulletin, 2019)

Differential magnitude of rhizosphere effects on soil aggregation at three stages of subtropical secondary forest successions - Ruiqiang Liu; Xuhui Zhou; Jiawei Wang; Junjiong Shao; Yuling Fu; Chao Liang; Enrong Yan; Xiaoyong Chen; Xihua Wang; Shahla Hosseini Bai (Plant and Soil, 2019)

Exogenous salicylic acid regulates reactive oxygen species metabolism and ascorbate–glutathione cycle in Nitraria tangutorum Bobr. under salinity stress - Yongqing Yan; Chenhui Pan; Yuling Du; Danyang Li; Wei Liu (Physiology and Molecular Biology of Plants, 2018)

Microcystin Bioaccumulation in Freshwater Fish at Different Trophic Levels from the Eutrophic Lake Chaohu, China - Yan Jiang; Yunmeng Yang; Yuling Wu; Jianbin Tao; Bo Cheng (Bulletin of Environmental Contamination and Toxicology, 2017)

Erratum to: Increase male genital diseases morbidity linked to informal electronic waste recycling in Guiyu, China - Xijin Xu; Yuling Zhang; Taofeek Akangbe Yekeen; Yan Li; Bingrong Zhuang; Xia Huo (Environmental Science and Pollution Research, 2014)

Increase male genital diseases morbidity linked to informal electronic waste recycling in Guiyu, China - Xijin Xu; Yuling Zhang; Taofeek Akangbe Yekeen; Yan Li; Bingrong Zhuang; Xia Huo (Environmental Science and Pollution Research, 2014)

Induction of apoptosis in HepG2 cells by polysaccharide MEP-II from the fermentation broth of Morchella esculenta - Meili Hu; Yan Chen; Cui Wang; Huali Cui; Peilu Duan; Tianlong Zhai; Yuling Yang; Shaofei Li (Biotechnology Letters, 2013)

High-level expression and characterization of a highly thermostable chitosanase from Aspergillus fumigatus in Pichia pastoris - Xiaomei Chen; Chao Zhai; Lixin Kang; Chunhua Li; Hong Yan; Yuling Zhou; Xiaolan Yu; Lixin Ma (Biotechnology Letters, 2012)

High glucose induced rat aorta vascular smooth muscle cell oxidative injury: involvement of protein tyrosine nitration - Yuling Zhao; Naihao Lu; Yan Zhang; Zhonghong Gao (Journal of Physiology and Biochemistry, 2011)

High glucose induced human umbilical vein endothelial cell injury: involvement of protein tyrosine nitration - Yuling Zhao; Naihao Lu; Hailing Li; Yan Zhang; Zhonghong Gao; Yuefa Gong (Molecular and Cellular Biochemistry, 2008)

A gene encoding alanine racemase is involved in spore germination in Bacillus thuringiensis - Xiaohua Yan; Yuling Gai; Liang Liang; Gang Liu; Huarong Tan (Archives of Microbiology, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)